THE PHO-2A MUTANT OF NEUROSPORA-CRASSA WHICH IS DEFICIENT IN PI-REPRESSIBLE ALKALINE-PHOSPHATASE (EC 3.1.3.1) IS ALSO DEFECTIVE IN PI-REPRESSIBLE ACID-PHOSPHATASE (EC 3.1.3.2) - Han, S. W.; Maccheroni, W.; Rossi, A. (Associação Brasileira de Divulgação Científica (ABRADIC), 1992)
1. The mycelial Pi-repressible acid phosphatase presented p-nitrophenylphosphatase activity with negative cooperativity and Michaelian behavior when synthesized by the wild-type and pho-2A mutant strains of Neurospora crassa, respectively.2. The major acid phosphatase present in cell extracts of the pho-2A mutant of N. crassa grown in low Pi medium is more thermolabile (t1/2 = 4 min at 54-degrees-C, pH 5.4) than that of the wild strain (stable for at least 80 min at 54-degrees-C, pH 5.4).3. The pho-2A mutant of N. crassa secreted a more thermolabile acid phosphatase (t1/2 = 30 min at 50-degrees-C, pH 5.4) than the wild strain (t1/2 of at least 80 min at 50-degrees-C, pH 5.4).4. The pho-2A mutant of N. crassa synthesized a more thermolabile acid phosphatase (t1/2 = 37 min at 54-degrees-C, pH 5.4) than the wild strain in high Pi medium (t1/2 = 14 min al 54-degrees-C, pH 5.4).5. The pleiotropic nature of the pho-2 locus and its possible involvement in the mechanism of phosphatase secretion by N. crassa are proposed.
Keywords: FUNGI; NEUROSPORA-CRASSA; ALKALINE PHOSPHATASE; ENZYME SECRETION; ACID PHOSPHATASE; P-NITROPHENYLPHOSPHATE